An industrial psychological study of the diversity phenomenon amongst managers in selected organisations - Vos, H. D.(Henry Daniel) (Stellenbosch : Stellenbosch University, 2012)
Dissertations (Ph. D.) -- University of Stellenbosch, 1998.